Top Health Issues: Pakistan and World. - Anwar Ali Jamali, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2020)
The United Nations (UN) right now records 18 ”Worldwide Issues". This isn't expected to be a comprehensive rundown. Or maybe, it fills in as a review of a portion of the significant issues every worldwide resident ought to know about. The UN has likewise defined 17 objectives to be accomplished by 2030. The United Nations had planned certain valid goals for the human progress in health sector, they indicated seventeen basic achievements that are necessary for human development in different sectors for all nations worldwide. Especially health and environment.